Deixis as a symbolic phenomenon - West, Donna E. (Linguistik Online, 2011)
Children’s early development of demonstrative use emanates directly from indexical gestures, namely, eye gaze, pointing, prehensile reaching, and giving exchanges. These indexical gestures become social in that they are joint attentional, and mark the inception of deictic use. Although children’s deictic use draws upon index as a directional and social phenomenon, early uses of index alone do not deliver any semantic/lexical/symbolic determinants to the mix. The distinctive premise here is that deictics, especially demonstratives, are not merely social, but symbolic from a Peircian perspective, especially in light of developmental findings (West 1986, 1987, 2010; Tanz 2009) indicating an acquisitional pattern of non-contrastive to contrastive uses of "this" and "that" from 3;0–4;9. While initial non-contrastive uses of demonstratives are directional and/or social, contrastive use after 3;0 requires apprehension of symbolic role taking/role shifting. In addition to delivering the indexical and/or social, deictic indicators must implicitly refer to a class (Nunberg 1993, 1995), e.g., near/far objects from speaker’s perspective in the case of demonstratives, and must ultimately have the potential to contrast objects/places with respect to distinctive points of orientation. These components together illustrate how mastery of deictic indicators is both a socio-pragmatic and semantic enterprise. In addition to indexing objects and securing joint attention with gesture, deixis requires semiotic and semantically based orientational competencies to shift perspectives and speech situation roles.